The Ability of Combined Flavonol and Trihydroxyorganic Acid to Suppress SARS-CoV-2 Reproduction - Andrey Bogoyavlenskiy; Pavel Alexyuk; Madina Alexyuk; Vladimir Berezin; Irina Zaitseva; Elmira Omirtaeva; Adolat Manakbayeva; Yergali Moldakhanov; Elmira Anarkulova; Anar Imangazy; Kuralay Akanova; Zhumagali Koshemetov; et al. (Viruses)
The global burden of COVID-19 continues to rise, and despite significant progress in vaccine development, there remains a critical need for effective treatments for the severe inflammation and acute lung injury associated with SARS-CoV-2 infection. In this study, we explored the antiviral properties of a plant-derived complex consisting of flavonol and hydroxyorganic acid compounds. Our research focused on the ability of the flavonol and hydroxyorganic acid complex to suppress the activity of several key proteins involved in the replication and maturation of SARS-CoV-2. These proteins include ACE2 protein, HRV 3C Protease, and Mpro (Main Protease). It was shown that the plant-based complex effectively inhibited the activity of these viral proteins. In addition to its effects on viral proteins, the flavonol and hydroxyorganic acid complex were shown to suppress viral replication in Vero E6 cells. At a dose of 22 μg/mL, the drug demonstrated maximum antiviral activity, significantly reducing the replication of SARS-CoV-2 in vitro. In preliminary studies, the complex showed both prophylactic and therapeutic potential, suggesting that it may be useful for preventing infection, as well as reducing the severity of disease once an individual has been infected with SARS-CoV-2. Based on the compelling results of this study, we propose the flavonol and hydroxyorganic acid complex as a potential therapeutic compound for SARS-CoV-2. Its ability to inhibit key viral proteins, suppress viral replication and exhibit protective and therapeutic effects positions it as a valuable candidate for further research and clinical evaluation. As the global fight against SARS-CoV-2 continues, plant-based therapies like this complex could complement existing treatments and provide new options for managing and treating the disease.